The lift snorkel technique for type Ia endoleak after fenestrated endovascular aneurysm repair of a juxtarenal abdominal aortic aneurysm - Eisaku Ito; Takao Ohki; Naoki Toya; Hikaru Nakagawa; Ryou Nishide; Kohei Okazaki; Tadashi Akiba (Surgical Case Reports)
Abstract Background The snorkel technique for a juxtarenal abdominal aortic aneurysm (JAAA) is an important treatment option for high-risk patients. We report the lift snorkel technique through the trans-femoral access for a type Ia endoleak after fenestrated endovascular aneurysm repair (FEVAR) in a case of difficult trans-brachial access. Case presentation A 76-year-old woman who had JAAA presented with a type Ia endoleak and sac expansion after FEVAR. We planned for proximal additional stentgraft with the bilateral renal artery snorkel technique. However, during the secondary intervention, it was difficult to cannulate to the left renal artery through the trans-brachial access due to interference of the supra-renal stent. Stentgraft was eventually delivered into the left renal artery via the trans-femoral access with a 5 Fr sheath. A plain angioplasty balloon was inserted coaxially through the sheath. The balloon was inflated in the proximal end of the stentgraft and then pushed up to replace the proximal end from down to up. The additional aortic cuff was deployed parallel to the snorkel stentgraft. One year after the additional treatment, computed tomography (CT) revealed aneurysm sac shrinkage. Conclusion The lift snorkel technique is a unique method converting the retrograde approach to antegrade renal artery stenting and would be an effective option for difficult trans-brachial cases for a type Ia endoleak after FEVAR of a JAAA.